2012
DOI: 10.1007/s11524-012-9726-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Identification in a High-Risk Urban Population: Does Automated eGFR Reporting Make a Difference?

Abstract: Whether automated estimated glomerular filtration rate (eGFR) reporting for patients is associated with improved provider recognition of chronic kidney disease (CKD), as measured by diagnostic coding of CKD in those with laboratory evidence of the disease, has not been explored in a poor, ethnically diverse, highrisk urban patient population. A retrospective cohort of 237 adult patients (≥20 years) with incident CKD (≥1 eGFR ≥60 ml/min/1.73 m 2 , followed by ≥2 eGFRs G60 ml/min/1.73 m 2 ≥3 months apart)-pre-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This may be in keeping with a prospective longterm study that found that high adiponectin is a novel independent predictor of CKD disease progression in men but not in women (Kollerits, Fliser, Heid, Ritz, & Kronenberg, 2007) and that adiponectin showed a strong positive correlation with age (Higashiura et al, 2004). This is consistent with previous studies that found that MetS is a significant determinant of kidney function in men (Tanaka, Shiohira, Uezu, Higa, & Iseki, 2006) and that female gender and increased age were associated with a lower progressive reduction of eGFR (Plantinga, Tuot, Grubbs, Hsu, & Powe, 2012). Our findings also echo the work of Eriksen and Ingebretsen (2006), who show that females have a slower progression of reduced kidney function.…”
Section: Discussionsupporting
confidence: 91%
“…This may be in keeping with a prospective longterm study that found that high adiponectin is a novel independent predictor of CKD disease progression in men but not in women (Kollerits, Fliser, Heid, Ritz, & Kronenberg, 2007) and that adiponectin showed a strong positive correlation with age (Higashiura et al, 2004). This is consistent with previous studies that found that MetS is a significant determinant of kidney function in men (Tanaka, Shiohira, Uezu, Higa, & Iseki, 2006) and that female gender and increased age were associated with a lower progressive reduction of eGFR (Plantinga, Tuot, Grubbs, Hsu, & Powe, 2012). Our findings also echo the work of Eriksen and Ingebretsen (2006), who show that females have a slower progression of reduced kidney function.…”
Section: Discussionsupporting
confidence: 91%
“…2023 Among a multi-specialty group practice of 15 health centers, about 25% of the 12,000 patients with CKD had it listed in the problem list. 22 In an urban setting with a high risk population nearly 50% of the 300 patients with CKD had ICD-9 coding documentation.…”
Section: Discussionmentioning
confidence: 99%
“…22 In an urban setting with a high risk population nearly 50% of the 300 patients with CKD had ICD-9 coding documentation. 23 Through chart review of nearly 900 patients with an eGFR < 60 being cared for in rural practices a study found less than 50% with documented CKD, even among those with high risk conditions such as hypertension and diabetes. 24 Similar to our finding of increased recognition with advanced CKD, a PCP practice based research network with nearly 35,000 CKD patients, found very low documentation of diagnosis among early CKD eGFR 45–59 (<10%), but higher documentation among CKD eGFR 30–44 (54%) and eGFR15-29 (54%).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The treatment burden of CKD may be particularly difficult to manage for lowincome populations that also have a higher risk of developing CKD and its complications. 14,15 Compared to the general population, these groups are more likely to live in disadvantaged neighborhoods and experience limited access to health care resources, low educational opportunities, and chronic unemployment. 16 These social determinants of health have a deleterious impact on an individual's ability to manage a chronic illness that requires consistent self-monitoring, adherence to regular medical care, and dietary and lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%